A Study on the Design and Analysis of Solar Photovoltaic Systems Using MATLAB - Loh, Wenn Shiuan; Asmawi, Rosli (Research Progress in Mechanical and Manufacturing Engineering, 2025)
This study focuses on the design and modelling of a photovoltaic (PV) system using MATLAB/Simulink, with the primary goal of optimizing system performance through the implementation of the Maximum Power Point Tracking (MPPT) technique. The project investigates the impact of solar irradiance and temperature variations on system performance under two simulation scenarios. Scenario one involves testing the PV system at three irradiance levels (200 W/m², 500 W/m², and 800 W/m²) with a fixed temperature. Scenario two fixes irradiance and varies the temperature (25°C, 30°C, 35°C). The simulations incorporate a Perturb and Observe (P&O) MPPT algorithm to maximize power extraction. The results demonstrate a strong correlation between irradiance levels and PV output, while temperature effects were comparatively minimal. This work contributes to developing more efficient PV systems for residential and small-scale industrial applications.